Fock space multi-reference coupled-cluster method for energies and energy derivatives - Pal, Sourav (Molecular Physics, 2010)
In this article, the development of Fock space multi-reference coupled-cluster method is reviewed. Molecular applications of the method for excitation and ionisation energies which took place at Quantum Theory Project have been discussed. Later developments of the method for energy derivatives have been presented along with pilot applications of molecular properties of radicals and excited states.
Keywords: coupled-cluster; difference energies; energy derivatives; Fock space; Multi-reference